NEODYMIUM ISOTOPIC VARIATIONS IN NORTHWEST PACIFIC WATERS - Amakawa H.; Nozaki Y.; Alibo D.S.; Zhang J.; Fukugawa K.; Nagai H. (My University, 2004)
Four vertical profiles of the concentration and isotopic composition of Nd in seawater were obtained in the western North Pacific. Two profiles from the Kuroshio Current regime showed congruently that although the Nd concentration increases gradually with depth, its isotopic composition varies significantly with depth depending upon the water mass occupying the water column. The high-salinity Kuroshio waters originating from the North Pacific Tropical Water (NPTW) carry the least radiogenic Nd (ϵNd = −7.4 to −8.7) to this region at ∼250 m from the western margin continental shelves, most likely from the East China Sea. The Nd isotopic compositions in the North Pacific Intermediate Water (NPIW) that occurs at 600 to 1000 m in the subtropical region are fairly uniform at ϵNd = −3.7. The profile data from the ∼38° to 40°N Kuroshio/Oyashio mixed water region off Sanriku of Honshu, Japan, also suggest that the newest NPIW with ϵNd = −3.2 is formed there by the mixing of various source waters, and the radiogenic component of Nd is derived mainly from the Oyashio waters.